Adaptive-Sliding-Window-Based Detection for Noncooperative Spectrum Sensing in Radar Band - Noh, Jiyoon; Kwon, Yohan; Lee, Juhyung; Baek, Hoki; Lim, Jaesung (IEEE Systems Journal, 2022)
Recently, radar frequency bands have attracted attention as candidates for cognitive radio owing to their wide bandwidth but low utilization. When spectrum sensing is performed in radar bands, sliding-window-based detection can be used to exploit the sparsity of the radar pulse signal in the time domain and obtain a sufficient number of samples. The detection performance and sensing time depend on the configuration of the windows. The detection performance was optimized when the window size was equal to the pulsewidth. However, the pulsewidth is generally unknown. Another way to increase the detection performance is to obtain more samples of the window. However, this causes large computation overhead owing to the sparsity of radar signals. Therefore, we propose an adaptive-sliding-window-based detection scheme to address these problems. First, the window is adaptively applied. Second, a pulsewidth estimation algorithm is proposed to approximate the window size to the pulsewidth for each detection. Additionally, we demonstrate the performance improvement of the proposed scheme and evaluate the estimation error of the proposed algorithm via simulations.
Keywords: Adaptive sliding windows; Cognitive radio; Detection performance; Pulsewidths; Radar bands; Radar detection; Radars antennas; Sliding Window; Sliding window-based; Spectrum sensing; Cognitive radio (CR); radar; sliding window; spectrum sensing